The Effect of Information Sharing and Trust on Supply Chain Management Performance with Long-Term Relationship as A Mediator: Evidence from SMEs in Yogyakarta - Puspitasari, Saniyah (Universitas Pelita Harapan, 2025)
This study investigates the effect of information sharing and trust on supply chain management (SCM) performance, with long-term relationship as a mediating variable. A census sampling technique was applied to 45 Small and Medium Enterprises (SMEs) in Yogyakarta’s Bakpia industry. Data was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that information sharing (β = 0.405) and trust (β = 0.410) significantly influence long-term relationships. Long-term relationships, in turn, have a strong positive effect on SCM performance (β = 0.378). Information sharing also directly affects SCM performance (β = 0.367), while trust shows a weaker direct effect (β = 0.212). Indirectly, both information sharing (β = 0.149) and trust (β = 0.151) contribute to SCM performance through long-term relationships as a mediator. The total effect analysis further highlights that information sharing (β = 0.578) and trust (β = 0.499) enhance SCM performance, with long-term relationship showing the highest total effect (β = 1.149). These findings emphasize the critical mediating role of long-term relationships in strengthening supply chain collaboration, particularly where trust alone may not directly drive performance. The study contributes to SCM literature by providing empirical evidence from SMEs in the traditional food sector and offers practical implications for managers to prioritize both transparent information exchange and sustainable partnerships to improve supply chain outcomes.